(3QSGdI aj JaSjQ CdaGX jcKQ JOGhdgG aj GdcJHs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg GdebOeI ef ebOeI (B() (3ddLeGYI GdeJbOeI efgG bGd GdTjN SYO GdOjf QMeg Gddgs
(3BNQgG (B:s
(3eef YGT cPdc ef GdUMGHI dHjO Hf QHjYI hChS Hf eYf GdSYOj hPcQ GHf SYO YOj GHf MGJe GdWGFj hPcQ GHf bJjHI fhad Hf eYGhjIs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B867(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 301s
(3eYLe GdeDdajf(B: 2 / 82s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GddZIs